(untitled) (Research, Society and Development, 2025)
Metformin is a widely used medication in the treatment of type 2 diabetes, a chronic condition that affects millions of people worldwide. Recognized for its effectiveness in reducing blood glucose levels and its safety profile, metformin is considered first-line therapy and is widely recommended. To verify the quality and equivalence of metformin tablets, physicochemical quality control was performed on generic and reference tablets. The samples were subjected to identification and disintegration tests, in addition to content determination using high-performance liquid chromatography (HPLC), which offers greater sensitivity and accuracy in the detection and quantification of the active ingredient. The tests demonstrated that the analyzed samples met the established pharmacopoeial parameters. Therefore, conducting tests to assess the physicochemical quality of pharmaceutical formulations is essential and must be closely monitored to ensure the quality of the manufactured products and minimize harm to the society that requires safe and effective treatments.